Precision Health for Chagas Disease: Integrating Parasite and Host Factors to Predict Outcome of Infection and Response to Therapy - Martinez, Santiago J.; Romano, Patricia S.; Engman, David M. (Frontiers in Cellular and Infection Microbiology, 2020)
Chagas disease is a disease of the heart (cardiomyopathy) or gastrointestinal tract (megaesophagus or megacolon) that develops in approximately one-third of people infected with the protozoan parasite Trypanosoma cruzi. T. cruzi is a zoonosis transmitted among animals and people through contact with triatomine bugs, which are found in much of the western hemisphere, including vast areas of the United States. The epidemiology and pathogenesis of Chagas disease are both highly complex, and much is known about both.However, it is still impossible to predict what will happen in an individual person infected with T.cruzi, because of tremendous variability in clonal parasite virulence and human susceptibility to infection, with no definitive molecular predictors of outcome from either side of the host-parasite equation. Despite much research on drug discovery for T. cruzi, there remain only two related agents in widespread use. In this Minireview we will briefly discuss the current state of Chagas diagnosis and prognosis and look forward to the day when it will be possible to employ precision health to predict disease outcome and determine whether and when treatment of infection may be necessary.